Efek Andrographolide terhadap Gambaran Histopatologi Sel Hepar Tikus Putih (Rattus norvegicus) Jantan Galur Wistar yang Diinduksi Karbon Tetraklorida (CCl4): Hasil Penelitian - Sanjaya, Vincent; Andriani; Ilmiawan, Muhammad In’am (Cermin Dunia Kedokteran, 2025)
Introduction: Andrographolide is a group of diterpene lactone isolates from the Andrographis paniculata plant with hepatoprotective properties. Andrographolide gives a hydrogen ion to pair with a free electron from a free radical to form a stable chemical compound and thus decrease liver damage. Methods: This experimental research used a post-test only with a control group design. The samples were mouse's liver (Rattus norvegicus).Twenty-four mice (Rattus norvegicus) were divided into 6 groups: a normal group, a curcumin-treated group as a positive control, a carbon tetrachloride-only group as a negative control, and the treatment group with the dose an andrographolide 50 mg/kgBW group, an andrographolide 100 mg/kgBW group, and an andrographolide 200 mg/kgBW group with 4 mice in each group. Mice were induced with carbon tetrachloride on the first day, then treated with curcumin and andrographolide for 7 days. Liver organs were dissected on day 9 to prepare a specimen for assessing hepatocyte damage (necrosis and hydropic degeneration). Results: Andrographolide showed a hepatoprotective effect on hepatocyte damage after induction by CCl4. The injury score in the normal group is 16.84; the negative control group is 34.36; the positive control group is 11.48; the dose 1 group is 24.92; the dose 2 group is 19.96; and dose 3 is 19.52. In the LSD test, the 50 mg/kgBW and 100 mg/kgBW andrographolide dose groups showed significant differences in hepatocyte damage compared to the normal group. There was no significant difference in liver histopathologic injury score between the normal group and the andrographolide 200 mg/kgBW group (ANOVA, p > 0.05). Conclusion: The best hepatoprotective effect was provided by andrographolide 200 mg/kgBW because the degree of damage is similar to that in the normal group.